Iris atrophy in patients with newly diagnosed multibacillary leprosy: at diagnosis, during and after completion of multidrug treatment. Issue 8 (15th November 2006) - Daniel, Ebenezer; Sundar Rao, P S S; ffytche, Timothy J; Chacko, Shirley; Prasanth, Hannah Ranjee; Courtright, Paul
Abstract : Aim: To describe the prevalence and incidence of iris atrophy in patients with multibacillary (MB) leprosy. Methods and patients: Prospective longitudinal cohort study. 301 newly diagnosed patients with MB leprosy were followed up during the 2 years of treatment with multidrug therapy (MDT) and for a further 5 years with biannual ocular examinations. Incidence of iris atrophy was calculated as the number of patients with iris atrophy per person-year (PY) of follow-up among those who did not have iris atrophy at baseline. Stepwise multiple regression confirmed the presence of specific associations of demographic and clinical characteristics (p<0.05) with iris atrophy, detected by univariate analysis. Results: Iris atrophy was present in 6 (2%) patients at enrolment. During MDT, with 445 PYs of follow-up, 9 patients developed iris atrophy (IR 0.02, 95% CI 0.01 to 0.04) that was associated with cataract (HR 15.13, 95% CI 3.71 to 61.79, p<0.001) and corneal opacities (HR 6.83, 95% CI 1.62 to 28.8, p = 0.009). After MDT, with 2005 PYs of follow-up, 60 patients developed iris atrophy (IR 0.03, 95% CI 0.023 to 0.039) that was associated with age (per decade; HR 1.40, 95% CI 1.10 to 1.78, p = 0.006), skin smear positivity (HR 3.50, 95% CI 1.33 to 9.24, p = 0.011), cataract (HR 3.66, 95% CI 1.85 to 7.25, p<0.001), keratic precipitates (HR 2.76, 95% CI 1.02 to 7.47, p = 0.046) and corneal opacity (HR 3.95, 95% CI 1.86 to 8.38, p<0.001). Conclusions: Iris atrophy continues to develop in 3% of patients with MB leprosy every year after they complete a 2-year course of MDT, and is associated with age, increasing loads of mycobacteria, subclinical inflammation, cataract and corneal opacity.